Chemical oxygen demand and biochemical oxygen demand analysis of discharge waters from laundry industry: monitoring, temporal variability, and biodegradability - Lacalamita, Dario; Mongioví, Chiara; Crini, Grégorio (Frontiers in Environmental Science, 2024)
In Europe, chemical oxygen demand (COD) and biochemical oxygen demand (BOD5) are used as organic indicators for the analytical characterization of laundry water. However, the values of these indicators are derived from one-off analytical measurements at a defined frequency. In addition, there are few data on the temporal variability of COD and BOD5 parameters and on water biodegradability beyond 5 days. In this work, samples of physicochemical treated wastewater were collected for one year and their content in COD and BOD5 measured, with BOD monitored over 35 days. The results showed that, for the 24 samples studied, the average and standard deviation values were 835 ± 176 mg/L for COD and 445 ± 114 mg/L for BOD5, indicating a biodegradability index of 2.0 ± 0.4. The interpretation of the data also indicated that the concentrations were close to emission limit value, particularly for BOD5. BOD21 values were particularly high compared to the initial COD, indicating the biodegradability of water.Laundry effluents were also rich in substances very quickly biodegradable, which has been demonstrated by the values of the ratio between BOD7 and BOD5. However, a significant proportion of surfactants is not degraded, as shown by measurements of total organic carbon and anionic surfactant analysis. The results of this study could help the industrial partner involved in our project to guide its choice of the complementary method to better treat wastewater and to reduce its organic load.